مقومات شعر الغزل عند الحار دلو - د الفضل إبراهيم الصادق علي; د. محمد عبد القادر الأمين (White Nile Journal for Studies and Research, 2014)
This study is aimed to shedlight on the characteristics of flirtation in Alhadalws life. As he considers as a pioneer of the public arts in Sudan. The significance of the study emerges from that. the flirtation poetry has received great attention from Arabic poet in all times. The Sudanese poets have a great impact in this domain. The study follows the analytical and descriptive approach. The study has some results. the importance ones are. Alhardalaw and as a result of his luxurious life, loved both servant and the free ones and he describe the servants without shyness. Also. he follows the approach of old ones in describing the she-beloved, as appointed nipple, soft lips and long hair In addition to that. Alhardalaw language is taken from the terminologies of his tribe which is kept for hundred years. The study has recommended to take Alhardalaw poetry from various angles.